Besarnya Gaya Normal Yang Terjadi Pada Sepasang Roda Gigi Lurus Karena Adanya Tekanan Yang Dihasilkan Roda Gigi Penggerak di Mesin Korin Type Ca-15 Di PT. XYZ - Yanto Yanto (JURNAL VOKASI TEKNIK, 2024)
PT. XYZ is an Indonesian company engaged in the production of snack foods, including chips, candy, noodles, crackers, and other packaged snacks. This study was conducted at the packing station using a Korin Type CA-15 packaging machine. The objective of this research was to determine the rotational performance of the Korin Type CA-15 machine and to analyze the normal force generated during its operation. The study employed a field research method by collecting primary data directly from the production site. Data were obtained through two techniques: interviews with the production supervisor and machine operators to gather operational information, and direct observations of the machine during production activities. Based on the analysis, the Korin Type CA-15 machine generated a tangential force of 22.639 kgf and a normal force of 24.091 kgf during operation. These results provide an overview of the machine's operating performance and can be used as a reference for evaluating its mechanical condition and operational efficiency.